The Samaritan version of Saadya Gaon's translation of the Pentateuch : critical edition and study of MS London BL OR7562 and related MSS - Zewi, Tamar. (Biblia Arabica, 2015)
This edition of MS London BL OR7562 and other related MSS, and the accompanying linguistic and philological study, discuss a Samaritan adaptation of Saadya's Judeo-Arabic translation of the Pentateuch, its main characteristics and place among other early Medieval Arabic Bible translations, viz., other versions of Saadya's translation of the Pentateuch, other Samaritan Arabic versions of the Pentateuch, and Christian and Karaite Arabic Bible translations. The study analyses the various components of this version, its transmission, its language, the extent to which the Samaritans adapted this version of Saadya's translation to their own version of the Hebrew Pentateuch, and their possible motives in choosing it for their own use.